Short-term repeated sprint training in hypoxia improves explosive power production capacity and repeated sprint ability in Japanese international-level male fencers: A case study - Hagiwara, M.; Yamagishi, T.; Okamoto, S.; Azuma, Y.; Yamashita, D. (Physiological Reports, 2023)
This case study reports the effects of six sessions of repeated sprint training in hypoxia (RSH) over 3 weeks on explosive power production capacity and repeated sprint ability (RSA) in two Japanese international-level foil fencers. The six RSH sessions (60-s sprints in total per session: consisting of two sets of five 6-s sprints with 30-s passive recovery, at simulated altitude of 3000 m) caused improvements of peak power output (PPO; Athlete A: 5.1%; Athlete B: 3.2%) and mean power output (MPO; Athlete A: 4.4%; Athlete B: 1.6%) over the 10 repeated sprints, respectively. The observed findings suggest that as few as six RSH sessions over 3 weeks can improve, at least to some extent, explosive power production capacity (PPO) and RSA (MPO) in the two elite fencers. To the best of our knowledge, this is the first study to apply short-term RSH in combat sport (fencing) with international-level athletes. Further studies are required to explore the effectiveness of short-term RSH in combat sports with a more robust study design (e.g., randomized control trial with adequate statistical power) as the modality of RSH would suit physical and physiological demands in the majority of combat sports (e.g., wrestling, boxing).